Evaluation of The “Sadar Pajak” Application Optimizing Local Tax Data in Surakarta, Indonesia - Kuncoro Aji, Anggit; Pratama, Raditya Hendra (Universitas Muhammadiyah Yogyakarta, 2025)
The application of information technology in regional tax management is crucial for improving the accuracy and efficiency of the tax system. Sadar Pajak, developed by the Regional Revenue Agency (Bapenda) of Surakarta City, represents an innovative approach that integrates technology with community participation in tax data updates. Unlike previous regional tax initiatives in Indonesia, this program uniquely combines crowdsourced taxpayer involvement with secure, standardized digital data management, making it the first local government application of its kind. Despite its potential, this program has received limited academic attention. This study evaluated the initiative using the CIPP (Context, Input, Process, Product) evaluation model, with a focus on system development, security, transparency, and technical standards. The results showed that the application meets all CIPP indicators, with a significant impact on improving data accuracy and potentially increasing PBB-P2 revenue. The application also meets security standards, including user authentication, access control, and data encryption, while supporting transparency in public information. Technically, the application is developed in accordance with KAK standards. The pilot project implementation in three sub-districts in 2023 demonstrated an improvement in building area data accuracy. To optimize its impact, strengthening socialization, utilizing digital technology, and enhancing collaboration between institutions and human resource capacity are recommended.